2015
DOI: 10.1245/s10434-015-4383-9
|View full text |Cite
|
Sign up to set email alerts
|

Ipsilateral Central Neck Dissection Plus Frozen Section Examination Versus Prophylactic Bilateral Central Neck Dissection in cN0 Papillary Thyroid Carcinoma

Abstract: FSE of ipsilateral nodes is accurate in determining nodal status, allowing the extension of the central neck clearance to be reliably modulated. Routine IpsiCCD plus FSE of the ipsilateral nodes could be a valid alternative to prophylactic BilCCD since it allows accurate staging and may reduce morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 30 publications
0
37
0
1
Order By: Relevance
“…Among these clinicopathological factors, ipsilateral central lymph node metastasis was strongly indicated to be the predictive factors. Raffaelli et al (36) reported that routine ipsilateral CND plus frozen section examination of the ipsilateral nodes may represent a valid alternative to prophylactic bilateral CND. As the rate of metastasis to the ipsilateral central neck is high, many metastatic lymph nodes are too small to be detected by frozen section examination, meaning that this strategy may aid prediction of contralateral central lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Among these clinicopathological factors, ipsilateral central lymph node metastasis was strongly indicated to be the predictive factors. Raffaelli et al (36) reported that routine ipsilateral CND plus frozen section examination of the ipsilateral nodes may represent a valid alternative to prophylactic bilateral CND. As the rate of metastasis to the ipsilateral central neck is high, many metastatic lymph nodes are too small to be detected by frozen section examination, meaning that this strategy may aid prediction of contralateral central lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, there are no preoperative parameters (age, gender, tumor size) to reliable identify an "at-risk" population who could benefit from a prophylactic central neck dissection [57]. Prophylactic ipsilateral central neck dissection with or without intraoperative pathology consultation on the nodes removed has been proposed for clinically unifocal and cN0 tumors, to reduce the risk of complications associated with prophylactic central neck dissection [54,[58][59][60]. Prophylactic lateral neck dissection in patients with differentiated thyroid carcinoma is not indicated.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Ayrıca rutin tek taraflı pCBD ve donmuş kesit incelemesinin evrelemeyi belirlemede iki taraflı pCBD'ye alternatif bir yöntem olabileceği ve morbiditeyi de azaltabileceğini ifade etmişlerdir. [58] Diğer yandan bu yöntemde yanlış negatiflik nedeninin klinik önemi sınırlı olan mikrometastazlardan kaynaklanabileceği yorumu da yapılmıştır. [57] Klavuzlara göz atıldığında ise 3 ayrı klavuzun farklı önerilerde bulunduğu görülür.…”
Section: Santral Boyun Diseksiyonu Genişliğiunclassified